Caso de estudio: importación de sistemas fotovoltaicos en la construcción industrial de viviendas modulares - Bosio Bobadilla, Jose Luis (2020)
The present work proposes and analyzes a business model for the construction sector through a construction company that provides housing to urbanization companies that work with the MiVivienda Fund. The economic growth of recent years, the dissatisfaction of the demand to obtain affordable housing and the facilities offered by the State through the MiVivienda Fund to enter the market through bonds and financing make our proposal not only sustainable but also attractive to venture into the item. Through a market, demand, supply and external supplier’s analysis we have proposed to have three projects a year in the study period. The first of 270 homes, the second of 300 and 350 for the last year. Thus, we have an industrial process of building modular homes. That is, houses that are built in a factory in parts and then taken to the land to be assembled. While, being suppliers of the urbanization companies in the lands awarded by the MiVivienda Fund, our factory can be mounted on the land itself, saving time, costs and making the logistics and construction process efficient. A third factor sets us apart. Our homes (90m2 for this work) have a photovoltaic system imported from Spain that supplies the home with electricity without connecting to a public energy network throughout the year. Planning in detail the operational processes of construction and import, we can create an efficient supply chain, which allows us to maintain a minimum storage and a constant import and operation in plant. With the strategies and analysis mentioned, and together with a group of 100 people, our construction process can be developed from beginning to end in 7 days, offering a quality product at an unreal final price for the current prices: USD 12,600. This price represents less than 50% of the maximum value of homes established by the MiVivienda Fund to be benefited by the housing bonus (MiVivienda, 2020). Thus, we have that our house of S / 41,580 at the exchange rate of S / 3.3 per USD, offers 52% profit margin to the urbanization company we provide and, in the case of selling our xvi homes to the final consumer directly, offers the end user a monthly fee cost of S / 173 considering an annual rate of 3% for three years.